PENINGKATAN PENGETAHUAN CARA PENINGKATAN PRODUKSI ASI MELALUI EDUKASI KONSELING TEMAN SEBAYA (PEER COUNSELING) - Juneris Aritonang; Ni Nyoman Sri Artina Dewi; Nettietalia Br Brahmana (JOMIS (Journal of Midwifery Science), 2023)
Exclusive breastfeeding for babies provides great benefits for the health status of babies and their mothers, but in reality the coverage of exclusive breastfeeding is still low. The low coverage of exclusive breastfeeding causes many problems such as stunted growth and development. The low coverage of exclusive breastfeeding is caused by the lack of knowledge of mothers about how to increase milk production. There are still breastfeeding mothers who are confused about how to breastfeed properly, how to increase milk production and how to deal with problems found during breastfeeding. Handling is needed in increasing this knowledge through peer counseling education. This research method is quasi-experimental with a one group pre-post test approach. The population in this study were third trimester pregnant women. The sampling technique was total sampling. All pregnant women who came to visit the LMT Siregar Clinic in September 2022 were used as research samples, namely 27 people. The purpose of this study was to examine the effectiveness of peer counseling education on increasing mother's knowledge in increasing milk production. The research location was at the Siregar LMT Clinic during August-November 2022. The results found that there was significant effectiveness in providing peer counseling education on mother's knowledge about increasing milk production at the Siregar LMT Clinic with a p-value of 0.023 (p-value <0.05). The recommendation in this study is that peers can be empowered in maternal and child health education methods in health services.